20=6(2+x)+8

Simple and best practice solution for 20=6(2+x)+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 20=6(2+x)+8 equation:


Simplifying
20 = 6(2 + x) + 8
20 = (2 * 6 + x * 6) + 8
20 = (12 + 6x) + 8

Reorder the terms:
20 = 12 + 8 + 6x

Combine like terms: 12 + 8 = 20
20 = 20 + 6x

Add '-20' to each side of the equation.
20 + -20 = 20 + -20 + 6x

Combine like terms: 20 + -20 = 0
0 = 20 + -20 + 6x

Combine like terms: 20 + -20 = 0
0 = 0 + 6x
0 = 6x

Solving
0 = 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
0 + -6x = 6x + -6x
Remove the zero:
-6x = 6x + -6x

Combine like terms: 6x + -6x = 0
-6x = 0

Divide each side by '-6'.
x = 0

Simplifying
x = 0

See similar equations:

| 743-28=x | | 4-3(2-2x)=4 | | x(x-2)(x+3)=0 | | 4(2-x)-7x=41 | | 1g+2=-6g+3+8g+4 | | (3x-5)(x^2-8x+7)=0 | | 8.4=1.2b | | 8-3x-(2x-5)=34x | | 4y-6=11y+57 | | 5x-3(x+5)=3x | | 27+27=x | | 1175.0508=2*3.14*r^2+2*3.14*r*23.4 | | -9(-3t+8)=-13t+48 | | 2e+6=3e-1 | | 1/2(k-5)=3 | | 4-8=3-5+n | | 7(-3x+7)=-(-3x+-73) | | 2x+43=34 | | M+14=3M-8 | | x^3+5x^2=6x | | m+7+4=-8 | | 5(x-7.2)=14.5 | | -(3x+2)=-19x+62 | | 25.748=2*3.14*r^2+2*3.14*r*3.1 | | 5a+10b=450 | | 453.6672=2*3.14*r^2+2*3.14*r*13 | | 5b+10a=450 | | -1-0.28v=2 | | 5*26=x | | -5+3(6-x)=1 | | 4x*3=99+x | | 20x=.6 |

Equations solver categories